Disturbance Characteristics of Induction Cooker on a Grid-Connected Photovoltaic System in Frequency Range of 9-150 kHz - Husnayain, Faiz; Tamim, Faizal; Sudiarto, Budi (JURNAL NASIONAL TEKNIK ELEKTRO, 2020)
This study aims to investigate the disturbance's characteristics induced by the induction cooker of the On-Grid PV System that is installed in the MRPQ at the Faculty of Engineering Universitas Indonesia (FTUI). In addition, this research is also to find out the behavior of the induction cooker on a frequency range of 9-15kHz. The load was connected to Switching Mode Power Supply (SMPS) that connected to the utility grid. Furthermore, the utilization of inverter that used SMPS technology may generate disturbance mostly at high frequency from 9 kHz to 150 kHz. Disturbance generated by each tool from the equipment in the PV system and household appliances may also affect each other in its operation. However, research and standardization regarding the effect of induction cooker disturbances on the PV system for frequency ranges of 9-150 kHz are still limited. Therefore, this research focuses on observing behavior and the characteristics of a disturbance generated by the induction cooker. There are two induction cookers investigated, brand A and B. The results show that the induction cooker generates disturbance at a frequency of 9-150 kHz, and the increased power used at the load will also increase the disturbance value. Furthermore, brand A has a more significant average incremental gradient compared to brand B induction cookers of 260% or 17.05mV / W for brand A and 6.58mV / W for brand B.Keywords: power quality, disturbance characteristics, induction cooker, on-grid photovoltaic, 9-150 kHz